2018
DOI: 10.2478/mmcks-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Examining the moderating effect of shopping value on private-label and loyalty in Indian grocery stores

Abstract: The present study has attempted to create and examine a conceptually grounded working model that examines the moderating influence of utilitarian and hedonic shopping values with Indian grocery stores on the association between usage of Private Label (PL) and Store Loyalty (SL). For this, primary data was collected from 350 consumers, from different stores in India selling PL products. The theoretical model was analyzed using SEM. The findings of the study reflect that an inverse relationship between PL usage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In this regard, the usage of social media may be a boon to these medical students as it gives access to numerous sources of information and supplements their mastery and understanding of the topics. This result is in line with the previous studies which have shown tremendous support for the role of students’ engagement in boosting the academic performance of the students (Hughes and Cao, 2018; Pekrun and Linnenbrink-Garcia, 2012; Klem and Connell, 2004; Bhat and Singh, 2018a, b, c).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this regard, the usage of social media may be a boon to these medical students as it gives access to numerous sources of information and supplements their mastery and understanding of the topics. This result is in line with the previous studies which have shown tremendous support for the role of students’ engagement in boosting the academic performance of the students (Hughes and Cao, 2018; Pekrun and Linnenbrink-Garcia, 2012; Klem and Connell, 2004; Bhat and Singh, 2018a, b, c).…”
Section: Discussionsupporting
confidence: 93%
“…The internal consistency of the questionnaire was also established through composite reliability. The values of coefficient of composite reliability range from 0.74 to 0.95, which was above the threshold value of 0.70 (Hoyle, 2012; Boomsma et al , 2012; Bhat and Singh, 2018a, b, c), therefore the internal consistency of the questionnaire was determined. Moreover, the AVE which ranges between 0.55 and 0.75, which is well above the thresh hold values of 0.50, therefore, the convergent validity was established.…”
Section: Resultsmentioning
confidence: 99%